Enhancing International Mindset in English Classes at a Japanese Music College: Impact of Integrating Documentary Photography and Piano Performance - Nakanishi, Chiharu; Yamamura, Kaoru; Thukral, Lily (Advances in Social Sciences Research Journal, 2023)
This study explores the impact of an innovative Japanese music college workshop incorporating documentary photography and piano performance to foster the students’ international mindset. In today’s globalized society, it is becoming increasingly crucial to facilitate intercultural exchange and mutual understanding. Harnessing the power of music presents an opportunity to bridge cultural divides, and this approach may be particularly beneficial within the unique cultural context of Japan. In high-context cultures like Japan, students may not always recognize the potential information gap between themselves and others. This information gap can lead to implicit communication, obstructing a comprehensive understanding of conveyed messages. Although previous research offers models and theories regarding intercultural receptivity and communication skills, there is a lack of studies focusing on the effects and methodologies of workshops blending documentary photography and piano performance, specifically within Japanese music colleges. Therefore, the present study conducts such a workshop and assesses its effectiveness by analyzing English reports from second-year students participating in the mandatory English class at a Japanese music college. The students’ level of English proficiency is CEFR A2. The assessment focuses on whether participants, from a low-context cultural perspective, can effectively express their individuality through originality by recognizing the differences in their information compared to others based on the information they acquire during the workshop. The results demonstrate an overall increase in students’ international awareness, with particularly high-performing students showcasing a deep understanding and insightful perspectives on the situation in Ukraine. This research aims to provide practical insights and directions for educators at Japanese music colleges to more meaningfully and effectively incorporate such workshops within their English curriculum.